Facile synthesis of three-dimensional spherical Ni(OH)2/NiCo2O4 heterojunctions as efficient bifunctional electrocatalysts for water splitting. (6th November 2020) - Sang, Yan; Cao, Xi; Wang, Lvxuan; Ding, Gaofei; Wang, Yingjie; Yu, Deshuang; Hao, Yanan; Li, Linlin; Peng, Shengjie
Abstract: Synthesis of highly efficient, non-noble and bi-functional electrocatalysts is exceedingly challenging and necessary for water splitting devices. In this work, three-dimensional spherical Ni(OH)2 /NiCo2 O4 heterojunctions are prepared by a one-step hydrothermal method and the hybrids are explored as efficient electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in an alkaline electrolyte via tuning different Ni/Co atomic ratios of heterojunctions. The optimized Ni(OH)2 /NiCo2 O4 (S (1:1)) exhibits high electrocatalytic activity with an ultralow over-potential of 189 mV at 10 mA cm −2 for the HER. With regard to the OER, the over-potential of the as-synthesized S (1:1) heterojunction is only 224 mV at the current density of 10 mA cm −2 . The improved catalytic performance of the Ni(OH)2 /NiCo2 O4 heterojunctions is attributed to the chemical synergic combining of Ni(OH)2 and NiCo2 O4, large specific surface area for exposing more accessible active sites, and heterointerface for activating the intermediates that facilitates electron/electrolyte transport. The prepared catalyst exhibits good durability and stability in HER and OER catalyzing conditions. This study provides a feasible approach for the building of highly efficient bifunctional water splitting electrocatalysts and stimulates the development of renewable energy conversion and storage devices. Highlights: The three-dimensional spherical Ni(OH)2 /NiCo2 O4 heterojunctions were constructed. The heterostructure would improve electrocatalytic performance. The optimized catalyst exhibits remarkable catalytic activity for water splitting. The S (1:1) heterojunction exhibits an overpotential of 224 mV for OER and 189 mV for HER.